Utilization of OSS, QRIS, and GMAPS Platform in Digitalizing MSEMs in Tamansari Village, Serang - Purbohastuti, Arum Wahyuni; Aribowo, Didik; Pertiwi, Widya Nur Bhakti; Kusyanto, Muhammad Johan Widi; Lusianingrum, Farah Putri Wenang (MOVE: Journal of Community Service and Engagement, 2025)
MSME players in Tamansari Village, Serang Regency still market their products conventionally. The objectives of this training include obtaining a business permit, making payments with Qris, and displaying business points on GMAPS. The method for carrying out activities in this service is training accompanied by assistance for direct practice and questions and answers. The training activities produced positive outcomes where MSME actors received business permits, registered with Qris, and displayed location points on GMAPS.